Developing a Modeling Framework to Simulate Compound Flooding: When Storm Surge Interacts With Riverine Flow - Loveland, Mark; Kiaghadi, Amin; Dawson, Clint N.; Rifai, Hanadi S.; Misra, Shubhra; Mosser, Helena; Parola, Alessandro (Frontiers in Climate, 2021)
Compound flooding is flooding by two or more sources; an example that we consider in this paper is coastal flooding due to a combination of storm surge and rainfall runoff. In recent years, such compound flood events have increased in frequency and magnitude, due to a number of factors including changing climate, sea-level rise, warming oceans, etc. Therefore, the ability to model such events is of increasing urgency. At present, there is no holistic, integrated modeling system capable of simulating compound flooding, leading to the need to couple various existing models. However, a big challenge in such a modeling effort is determining the primary model and the effect of nearby watersheds in amplifying the impact of compound flooding events. In this study, we investigated the possibility of using the Advanced Circulation (ADCIRC) model as the primary model for simulating compound floods. The performance of the ADCIRC model was compared with the Hydrologic Engineering Center- River Analysis System (HEC-RAS) model both at the watershed and global scales. Furthermore, the importance of including riverine discharges and the interactions among adjacent watersheds were quantified. Results showed that the ADCIRC model could reliably be used to model compound flooding. Moreover, the incorporation of river discharge is critical in accurately predicting flood patterns when high amounts of riverine flow occur in conjunction with storm surge. Particularly, with storms such as Hurricane Harvey (2017), where river flows were near record levels, inundation patterns and water surface elevations were highly dependent on the incorporation of the discharge input. Such an effect caused extra and longer inundations in some areas during Hurricane Harvey. Comparisons with real gauge data show that adding internal flow boundary conditions into ADCIRC to account for river discharge significantly improves accuracy in predictions of water surface elevations during coastal flooding events. Finally, the results suggest consideration of adjacent watersheds when modeling compound flooding is important, especially for areas farther upstream of the watershed outlets.